Pelanggaran Prinsip Kerja Sama dalam Film MY STUPID BOSS Karya Upi Avianto - Amelia Amanda Verawati; M. Nur Kholis; Taswirul Afkar (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to identify and describe the violations of the cooperative principle in the dialogues of the films My Stupid Boss and My Stupid Boss 2 directed by Upi Avianto, using Paul Grice’s conversational maxims as the analytical framework. The research employs a qualitative descriptive method with observation and note-taking techniques for data collection. The data were taken from character dialogues that indicated violations of the maxims of quantity, quality, relevance, and manner. The findings reveal that the most frequent violations occurred in the maxim of quantity, predominantly by the main character, Bossman. These violations do not always hinder communication but often generate conversational implicatures that reflect the character’s speech style, personality traits, and comedic effects.